Reply to "Electrical properties analysis of materials with ferroic order". Issue 25 (22nd February 2016) - Smari, M.; Rahmouni, H.; Elghoul, N.; Walha, I.; Dhahri, E.; Khirouni, K.
Abstract : Real part of dielectric permittivity of the compound La0.5 Ca0.2 Ag0.3 MnO3 as a function of temperature. The inset shows the plot of log(1/ ε ′ − 1/ ε ′m ) as a function of log( T − T m ) measured at 1 kHz. Abstract : We thank the authors for the interest they have given to our paper (M. Smari et al., RSC Advances, 2015, 5, 2177), but we find that their comment is oriented according to their previous work and to their own vision of data analysis.